Enhanced 2,3-butanediol recovery from fermentation broth: a study on isobutanol/sodium chloride aqueous two-phase systems - Gawal, Pramod Madhukar; Lataye, Sweta (Biotechnology and bioprocess engineering, 2025)
The extraction and recovery of 2,3-butanediol (2,3-BD) from the fermentation broth (FB) is a significant bottleneck in industrial production. Herein, we explore the hybrid aqueous two-phase extraction combined with distillation (HATPED) for recovering 2,3-BD from FB. Aqueous two-phase systems (ATPS) were selected for extraction of 2,3-BD from FB by distribution studies with different organic solvent/inorganic systems. The selected isobutanol/sodium chloride ATPS was optimized through a central composite design (CCD)-based response surface methodology (RSM) to evaluate the effects of solvent concentration, extraction temperature, and salt concentration on the 2,3-BD extraction efficiency ( Y ). The optimal extraction parameters (30% w/v sodium chloride, 40 °C, 35% v/v isobutanol) resulted in a distribution coefficient ( D ) of 7.03 and a ( Y ) of 87%, exceeding theoretical values by 0.080%. The organic phase was processed in the distillation unit to concentrate the 2,3-BD. Scale-up experiments showed impressive extraction and recovery rates of 98.74% and 97.38%, respectively (purity > 99%) in two cycles. Additionally, 85.5% of sodium chloride was recovered from the aqueous phase via evaporation. This economical and scalable approach offers valuable insights for 2,3-BD recovery from FB using organic solvent/inorganic salt via HATPED.